Are There Striking Differences in Outpatient Use of Antibiotics Between South Backa District, Serbia, and Some Scandinavian Countries? - Horvat, Olga; Mijatović, Vesna; Milijasević, Boris; Tomas, Ana; Kusturica, Milica Paut; Tomić, Zdenko; Sabo, Ana (Frontiers in Public Health, 2018)
There is little published information about antibiotic utilization in outpatients in Serbia. The objective of this study was to determine the amount and structure of outpatient antibiotic use in South Backa District (SBD) in Serbia, to assess prescibing quality of antibiotics and to compare with results from Scandinavian countries. Data on the antibiotic use were collected from all private and state-owned pharmacies from January through March 2008 in SBD. Results were expressed as the number of defined daily doses/1,000 inhabitants/day. The drug utilization 90% method was also used. Penicillins were the most frequently used antibiotic subgroup in SBD (35.20%), followed by cephalosporins (19.16%) and macrolides (13.18%). Thirteen drugs accounted for 90% of total antibiotics consumption (DU90% segment). The average cost/DDD within the DU90% segment was 0.95 euros, whereas the average cost/DDD beyond the DU90% segment was 1.89 euros, indicating that less expensive antibiotics were more frequently used. High use of ampicillin, third-generation cefalosporins, co-trimoxazole, and gentamicin, will aggravate the alarming problem of resistance in Serbia. Differences in the amount and structure of antibiotic consumption between SBD and Scandinavian countries indicate the need of updated national guidelines for rational antimicrobial drug use in Serbia.